METHODOLOGICAL ASPECTS OF COMPUTED TOMOGRAPHY ODONTOMORPHOMETRY OF BOYS AND GIRLS WITH THE PHYSIOLOGICAL BITE - Gunas, I. V.; Dmitriev, N. A.; Marchenko, A. V. (Journal of Education, Health and Sport, 2015)
Gunas I. V., Dmitriev N. A., Marchenko A. V. Methodological aspects of computed tomography odontomorphometry of boys and girls with the physiological bite. Journal of Education, Health and Sport. 2015;5(11):345-355. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.34097 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A345-355 https://pbn.nauka.gov.pl/works/670995 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 25.10.2015. Accepted: 20.11.2015. UDC 616.716.8-071-084:613.956: 617.52:62-408 METHODOLOGICAL ASPECTS OF COMPUTED TOMOGRAPHY ODONTOMORPHOMETRY OF BOYS AND GIRLS WITH THE PHYSIOLOGICAL BITE I.V. Gunas, *N.A. Dmitriev, **A.V. Marchenko International Academy of Integrative Anthropology, Vinnitsa; *Vinnitsa National Medical University named after Pirogov, Vinnitsa; **Ukrainian Medical Dental Academy, Poltava Summary The article presented data regarding the average mesiodistal, vestibulо-oral and vertical dimensions of the teeth of boys and girls fromUkraine, obtained using cone beam computed tomography. We have studied 101 tomograms, male (n = 44) and female (n = 57) between the ages from 18 to 25 years with orthognathic bite. For this investigation we used dental cone beam computer tomography - Veraviewepocs 3D, Morita. When comparing the performance of odontometric features of the similar teeth from right and left sides, no significant differences were found. Established population characteristics for mesiodistal, vestibulo-oral and vertical dimensions of the teeth for the boys and girls fromUkrainewith orthognathic bite. For most sizes of teeth (except mesiodistal size of the second lower premolar) showed significant differences (larger sizes in boys). Key words: odontometry, computed tomography, the size of the teeth. Резюме МЕТОДОЛОГІЧНІ АСПЕКТИ КОМП'ЮТЕРНО-ТОМОГРАФІЧНОЇ ОДОНТОМОРФОМЕТРІЇ У ЮНАКІВ ТА ДІВЧАТ З ФІЗІОЛОГІЧНИМ ПРИКУСОМ. У статті представлені дані щодо середньостатистичних мезіодистальних, вестибуло-оральних та вертикальних розмірів зубів у юнаків та дівчат України отриманих за допомогою конусно-променевої комп'ютерної томографії. Були вивчені 101 томограма представників чоловічої (n = 44) і жіночого (n = 57) статі у віці від 18 до 25 років з ортогнатичним прикусом. Для проведення даного дослідження використовували дентальний конусно-променевий комп'ютерний томограф - Veraviewepocs 3D, Morita. При порівнянні коп’ютернотомографічних метричних характеристик однойменних зубів правої і лівої сторін, достовірних відмінностей виявлено не було. Встановлені популяційні особливості мезіодистальних, вестибуло-оральних і вертикальних розмірів зубів для юнаків та дівчат України з ортогнатичним прикусом. Для більшості розмірів зубів (за винятком мезіодистального розміру другого нижнього премоляра) встановлені достовірні відмінності (більш великі розміри у юнаків). Ключові слова: одонтометрія, комп'ютерна томографія, розміри зубів. Резюме МЕТОДОЛОГИЧЕСКИЕ АСПЕКТЫ КОМПЬЮТЕРНО-ТОМОГРАФИЧЕСКОЙ ОДОНТОМОРФОМЕТРИИ У ЮНОШЕЙ И ДЕВУШЕК С ФИЗИОЛОГИЧЕСКИМ ПРИКУСОМ. В статье представлены данные относительно среднестатистических мезиодистальных, вестибуло-оральных и вертикальных размеров зубов у юношей и девушек Украины, полученных с помощью конусно-лучевой компьютерной томографии. Были изучены 101 томограмма представителей мужского (n=44) и женского (n=57) пола в возрасте от 18 до 25 лет с ортогнатическим прикусом. Для проведения данного исследования использовали дентальный конусно-лучевой компьютерный томограф – Veraviewepocs 3D, Morita. При сравнении копьютернотомографических метрических характеристик одноименных зубов правой и левой сторон, достоверных различий обнаружено не было. Установлены популяционные особенности мезиодистальных, вестибуло-оральных и вертикальных размеров зубов для юношей и девушек Украины с ортогнатическим прикусом. Для большинства размеров зубов (за исключением мезиодистального размера второго нижнего премоляра) установлены достоверные различия (большие размеры у юношей). Ключевые слова: одонтометрия, компьютерная томография, размеры зубов.